THE INFLUENCE OF COMPANY SIZE, SOLVENCY, PROFITABILITY AND AUDIT OPINION ON AUDIT DELAY (STUDY ON PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE IDX IN 2019-2023) - Silfia Citra; Rico Nur Ilham; Darmawati Muchtar; Nurlela (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This research aims to analyze the influence of company size, solvency, profitability, and audit opinion on audit delay in property and real estate companies listed on the IDX in 2019-2023. This research uses secondary data obtained from the financial reports of selected property and real estate companies using purposive sampling techniques. The sample from this research is 51 companies from 2019-2023 with 255 observations. The data analysis method used is panel data regression with a fixed effect model. The results show that company size, Debt To Asset Ratio (DAR) and audit opinion have a positive and insignificant effect on audit delay. Profitability as measured by Return On Assets (ROA) has an significant negative effect on audit delay, the higher the level of profitability, the smaller the audit delay.